Determination of psychological correlates of peak performance in developmental archers - Nurfatehah Mat Salleh, F.; Hashim, H. A.; Krasilshchikov, O. (Journal of Physical Education and Sport, 2020)
This study determined optimal zones of heartrate,anxiety intensity and arousal for archery performance among Malaysian elite developmental archers. Using a cross-sectional study design, nineteen archers (Mean age = 15.37± 1.5) participated in the study. Participants underwent three months of routine training session with two competitionswithin the three months. Throughout the training sessions and during competition, archers` heart rate, anxiety intensity, arousal level, and shooting performance were monitored. All parameters were measured weekly until end of the study. The revised Competitive State Anxiety-2 (CSAI-2R) and revised Sport Grid (Sport Grid - R) were used to measure competitive anxiety and arousal. In addition, Polar heart rate monitor (S710i, Polar Electro Oy, Finland) was used to monitor participants` heart rate. Cluster analysis was used to create the archers` performance profile and One Way ANOVA was used to compare the difference between the clusters. The results of ward method revealed a two-cluster profile. Profile 1 exhibits a low range of heart rate, but relatively high in shooting score and psychological variables. Profile 2 is characterized by high range of heart rate but low in shooting score and psychological variables. T-test results revealed significant differences between cluster group in shooting score, cognitive anxiety and somatic anxiety. It is concluded that better shooting score is associate with lower heart rate, lower arousal, higher self-confidence as well as higher in cognitive and somatic anxiety among archers in the current study.